Investigating the Effect of Oil and Gas Exports and Macroeconomic Variables on Gross Regional Domestic Product in Indonesia - Hidayat, Wahyu; Suriani, Suriani; Sartiyah, Sartiyah (Indonesia Academia Research Society, 2024)
This study examines the relationship between oil and gas exports, macroeconomic variables (such as inflation and population), and Indonesia's Gross Regional Domestic Product (GRDP). Specifically, it focuses on seven Indonesian provinces that are the largest oil and gas producers: Aceh, North Sumatra, South Sumatra, Riau, East Java, East Kalimantan, and Papua. Utilizing panel regression analysis, the study analyzes annual data from 2010 to 2022, sourced from the Indonesian Central Bureau of Statistics (BPS) and the respective BPS offices of each province. The findings reveal that oil and gas exports, and total population positively influence GRDP. At the same time, inflation negatively impacts GRDP, particularly in the leading oil and gas-producing regions. Based on these results, the study suggests that the government should consider offering fiscal incentives, such as tax reductions or import duty exemptions. It aims to attract domestic and foreign investment in exploration and production. Furthermore, it advocates for advancements in oil and gas processing technologies to enhance the quality and quantity of oil and gas exports, focusing on finished goods rather than relying solely on raw products.